Design of the optical tomography system for four projections CMOS linear image sensor [electronic resource] - Nur Hasanah Shafei, 1989- , author (2012)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik Perubatan))- Universiti Teknologi Malaysia, 2012